2019
DOI: 10.1098/rspb.2018.2740
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal variation in the production of vocal information about food supports a model of social adjustment in wild songbirds

Abstract: Wintering songbirds have been widely shown to make economic foraging decisions to manage the changing balance of risks from predation and starvation over the course of the day. In this study, we ask whether the communication and use of information about food availability differ throughout the day. First, we assessed temporal variation in food-related vocal information produced in foraging flocks of tits ( Paridae ) using audio recordings at radio-frequency identification-equipped feedin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 52 publications
(84 reference statements)
1
24
0
Order By: Relevance
“…Such decisions can alter transmission pathways and outcomes. For example, songbirds consider their social environment when producing vocal information to recruit new members to a foraging site (Suzuki & Kutsukake 2017;Hilleman et al 2019) When behaviours are socially-learned, shared within subgroups of the population, and persist over time, they are recognized as culture (Laland & Hoppitt 2003). Considering how learned behaviours can affect individual social decisions reveals the potential for culture to underpin the co-evolution between social structure and behaviour.…”
Section: Information and Cultural Transmissionmentioning
confidence: 99%
“…Such decisions can alter transmission pathways and outcomes. For example, songbirds consider their social environment when producing vocal information to recruit new members to a foraging site (Suzuki & Kutsukake 2017;Hilleman et al 2019) When behaviours are socially-learned, shared within subgroups of the population, and persist over time, they are recognized as culture (Laland & Hoppitt 2003). Considering how learned behaviours can affect individual social decisions reveals the potential for culture to underpin the co-evolution between social structure and behaviour.…”
Section: Information and Cultural Transmissionmentioning
confidence: 99%
“…Here, we study foraging behaviour in mixed-species flocks of tits to test whether individuals use 92 social information when assessing foraging patches. Tits and other species from the Paridae family 93 provide a good system for information diffusion experiments, because they readily use social 94 information in foraging contexts, from finding food (e.g., Sasvári1979; Farine et al 2015b;Firth et al 95 2016;Hillemann et al 2019a), to learning innovative foraging techniques (Aplin et al 2013(Aplin et al , 2015 96 and avoidance of unpalatable prey (Thorogood et al 2018). Further, it has been shown that 97 information does not spread between individuals at random but can be predicted by their connections 98 in the population-level social network (Aplin et al 2012;Farine et al 2015a;Firth et al 2016).…”
mentioning
confidence: 99%
“…Two access 179 holes to the feeder were fitted with RFID antennae (scanning rate: 16 Hz), recording the identity of all trial. Data from full-feeder trials were previously published in Hillemann et al 2019a, in…”
mentioning
confidence: 99%
See 2 more Smart Citations